The influence of physiological and pathological perturbations on blood-brain barrier function - Zhao, Nan; Chung, Tracy D.; Guo, Zhaobin; Jamieson, John J.; Liang, Lily; Linville, Raleigh M.; Pessell, Alex F.; Wang, Linus; Searson, Peter C. (Frontiers in Neuroscience, 2023)
The blood-brain barrier (BBB) is located at the interface between the vascular system and the brain parenchyma, and is responsible for communication with systemic circulation and peripheral tissues. BBB dysfunction is usually considered in the context of disease. During life, the BBB can be subjected to a wide range of perturbations or stresses that may be endogenous or exogenous, pathological or therapeutic, or intended or unintended. The risk factors for many diseases of the brain are multifactorial resulting in in different perturbations that may occur simultaneously (e.g. two-hit model for Alzheimer's disease) and result in different outcomes. Therefore, it is important to understand the influence of individual perturbations on BBB function in isolation . Here we review the effects of eight perturbations: mechanical forces, temperature, electromagnetic radiation, hypoxia, endogenous factors, exogenous factors, chemical factors, and pathogens. While some perturbations may result in acute or chronic BBB disruption, many are also exploited for diagnostic or therapeutic purposes. The resultant outcome on BBB function depends on the dose (or magnitude) and duration of the perturbation. Homeostasis may be restored by self-repair, for example, via processes such as proliferation of affected cells or angiogenesis to create new vasculature.Transient or sustained BBB dysfunction may result in acute or pathological symptoms, for example microhemorrhages or hypoperfusion. In more extreme cases, perturbations may lead to cytotoxicity and cell death, for example through exposure to cytotoxic plaques.